Childhood Stroke: A Cross-sectional Study in a Tertiary Level Hospital of Bangladesh (Ibrahim Cardiac Medical Journal, 2018)
Background & objective:The present study was undertaken to find the prevalence and pattern of childhood stroke and to see its clinical presentation and sub-types.Materials & Methods:The present cross sectional study was conducted in the Department of Pediatrics, BSMMU, Dhaka over a period of 6 months. A total of 30 children suffering from childhood stroke, provisionally diagnosed on the basis of clinical criteria and confirmed by neuroimaging were the study population.The demographic variables were age, sex, age at onset and age at case taking. The signs and symptoms at presentation, causes, investigations, neuro-imaging findings and final diagnosis were recorded.Result: Over half (53.4%) of the patients were in the range of 13 – 36 months with mean age of the patients being 39.1 ± 8.2 months. The mean age at onset was 36.2 ± 8.3 months. About 47% of patients were male and 53% female. Paresis of limb was invariably present, unconsciousness at onset (50%), convulsion (33.3%), aphasia (26.7%), raised blood pressure (23.3%), vomiting (13.3%), visual defect (8.7%) and headache (6.7%). Arterial occlusion was the main cause of childhood stroke (36.7%) followed by hypertensive encephalopathy (10%), migraine, hematoligical disease, cardiomyopathies (each 6.7%). Investigations revealed that over one-third (36.7%) of the patients had leucocytosis and 13.3% abnormal echocardiography. All the children either exhibited ischemia or infarction or hemorrhage on Computed Tomography (CT) and 86.7% on Magnetic Resonance Imaging (MRI). Seventy percent and 36.7% of patients had MRA and MRV abnormality respectively. About 47% of the patients had acute ischemic stroke, 13.3% AIS with left-sided haemiparesis with facial palsey and another 13.3% AIS with right-sided haemiparesia. Acute haemorragic stroke (AHS), acute stroke with Hb beta-thalassaemia, acute stroke with right-sided haemiparesis with cardiomyopathy and recurrent haemorragic stroke were rare.Conclusion: The study concluded that childhood stroke occurs most frequently between one to three years of age and equally affects male and female. Paresis of limb and unconsciousness at the onset were the main presenting features and arterial hypertension and hypertensive encephalopathy were the common cause of childhood stroke. Nearly three-quarters of the children present with ischemic stroke and the rest with haemorrhagic stroke.Ibrahim Card Med J 2016; 6 (1&2): 20-24